Testicular differentiation and development in South American catfish, surubim, Pseudoplatystoma fasciatum - Valentin, Fernanda N. [UNESP]; Nakaghi, Laura S. O. [UNESP]; Batlouni, Sergio R. [UNESP]; Nascimento, Nivaldo F. do [UNESP]; Faria Paes, Maria do Carmo [UNESP]; Silva, Regiane Cristina da [UNESP]; Manzini, Breno [UNESP]; Corchuelo Chavarro, Sheryll Yohana [UNESP]; Correa Assuncao, Marcelo Henrique [UNESP] (Wiley-Blackwell, 2019)
In the species Pseudoplatystoma fasciatum the males are smaller than females. Thus, the objective of this study was to describe the process of testicular differentiation and provide tools for sex manipulation techniques aimed at improving the productivity of farming of sexually-reversed females. Correlation between the length, age, sex rate and the stage of gonadal development were analyzed in this species from samples collected between 0 and 240 days post-hatching. Testicular differentiation was divided into eight stages, based on the cellular and morphological characteristics of the gonad. The results showed that sexual differentiation has a greater correlation to the size than the age in this species. This study provides knowledge on the proliferation and distinctive arrangement of somatic cells, which enabled the early identification of the testis due to the presence of future fringes in the specimens. Testicular differentiation in P. fasciatum was histologically different from other species due to the proliferation and distribution of somatic cells in the regions that would originate the testicular tubules and sperm ducts. Meiosis began at a later stage in comparison with other species, therefore, it was not considered a criterion for early sexual characterization. It can be concluded that testicular differentiation in P. fasciatum occurs relatively early and this data can be used to improve sex inversion protocols and increase productivity in this species.
Keywords: gonads; histology; somatic cells; testicular tubules